Biodegradation of Cyanogenic Glycoside of Cassava Leaves (Manihot esculenta Crantz) Via Fermentation as A Mean of Ruminant Feed Supply - Prayitno, CH; Suwarno, Suwarno; Rahardjo, T (ANIMAL PRODUCTION, 2011)
The development of ruminants must always be followed by forage sources as its feed. The usage of agro industrial by-product like cassava leaves is one of steps that can be conducted.Â  The purpose of this research was to study the effect of leaves-of-bitter-cassava fermentation using a mixture of Aspergillus niger-cattle bolus on the concentrations of HCN, crude protein, digestibilities of dry matter and organic matters.Â  Experimental method was used in this study, using completely randomized design with six treatments namely fresh and wilted leaves of bitter cassava, added with Aspergillus niger and 0, 2, 4, 6, and 8% of cattle bolus, each of which was repeated four times. The results showed that the mixture of Aspergillus niger-cattle bolus in cassava leaves had a highly significant effect on HCN, crude protein, dry matter and organic matter digestibilities. The conclusion of this research is that fermentation of leaves of bitter cassava with 6% of Aspergillus niger and cattle bolus is able to degrade cyanogenic glycoside and increase digestibility. (Animal Production 13(1):18-23 (2011)Key Words: cassava leaves, glycoside, Aspergillus, cattle-bolus.